SizaAtlas. Filling the gaps for World Heritage - Genin, Soraya M.; Ferreira, T. C.; Correia, M. (2024)
The SizaAtlas book is the result of the research project ‘SizaAtlas. Filling the Gaps for World Heritage’, which seeks primarily to contribute to the nomination of a group of Álvaro Siza’s architectural works for the World Heritage List. The book is structured in four chapters: (i) The SizaAtlas project, introducing the research and its main tasks; (ii) Extended abstracts presented at the final conference held at the FAUP - Faculdade de Arquitetura da Universidade do Porto, and at the book launch at the ISCTE - Instituto Universitário de Lisboa; (iii) An interview with Álvaro Siza about the Malagueira neighbourhood, his other social housing and projects; (iv) An inventory of 168 architectural works by Álvaro Siza (between 1954-2024), divided into two sections: Works in Portugal and International Works, presented geographically. The book is available online on the SizaAtlas platform, which displays the georeferenced inventory. It is complemented by eighteen illustrated booklets on the architectural works included in the Tentative World Heritage List, as well as archival and survey documentation, photogrammetry, 3D models and 360º virtual tours.